Development Strategy For Micro Small Business (Umk) During The Covid-19 Pandemic In Maluku Province - Jolyne Myrell Parera; Debby Likumahua; R Suryati Ismail (Trunojoyo University of Madura, 2021)
This research was conducted based on the reality of the research problem, where economic activity in SMEs is in a threatened position due to the COVID-19 pandemic. This study aims to analyze the internal and external sides of SMEs, measure financial stability and lending to banks, analyze whether credit provision has been efficient or not in improving banking performance for SMEs. In addition, strategic policy measures are taken through a roadmap for developing competitive and sustainable SMEs. The research method used is a survey method. The data obtained were processed based on the principles of descriptive statistics, namely the analysis of Non Performing Loans (NPL) to determine the ratio of NPL and the average NPL. The time period used for analysis needs is 2019 and 2020. The results of the SWOT analysis, Non Performing Loans (NPL), effectiveness and efficiency, indicate that banks have not been effective and not efficient in disbursing credit. This needs to be a concern for banks in disbursing credit to SMEs, by providing easy administrative requirements for SMEs proposing credit, so that SMEs can have business capital for the development of competitive and sustainable SMEs. On the other hand, the results of the NPL calculation are below 5%, this shows a healthy banking performance, meaning that there are no bad loans, as a result of relaxation and stimulus from the Government to SMEs when SMEs experience a chaotic situation due to the COVID-19 pandemic. Furthermore, a 5-year development plan was carried out, namely from 2020-2025, with the goal of strategic planning being competitive and sustainable SMEs based on e-commerce.